Plan optimization for mediastinal radiotherapy: Estimation of coronary arteries motion with ECG-gated cardiac imaging and creation of compensatory expansion margins. Issue 3 (June 2018) - Levis, Mario; De Luca, Viola; Fiandra, Christian; Veglia, Simona; Fava, Antonella; Gatti, Marco; Giorgi, Mauro; Bartoncini, Sara; Cadoni, Federica; Garabello, Domenica; Ragona, Riccardo; Filippi, Andrea Riccardo; et al.
Abstract: Background and purpose: Inadvertent heart and coronary arteries (CA) irradiation may increase the risk of coronary artery disease (CAD) in patients receiving thoracic irradiation. To date, the entity of cardiac-related CA displacement and the possible margins to be used for planning organs at risk volume (PRV) have been poorly described. Aim of this study was to quantify CA displacement and to estimate PRV through the use of ECG-gated computed tomography (CT) scans. Material and methods: Eight patients received an ECG-gated intravenous contrast enhanced CT for non-cancer related reasons. Nine data sets were reconstructed over the entire R–R cycle with a dedicated retrospective algorithm and the following structures were delineated: Left main trunk (LM), left anterior descending (LAD), left circumflex (CX) and right coronary artery (RCA). CA displacements across the different cardiac phases were evaluated in left–right (X), cranio-caudal (Y) and anteroposterior (Z) directions using the McKenzie–van Herk formula (1.3 * Σ + 0.5 * σ). Results: The following CA displacements were found in X, Y and Z coordinates: 3.6, 2.7 and 2.7 mm for LMT, respectively; 2.6, 5.0 and 6.8 mm for LAD, respectively; 3.5, 4.5 and 3.7 mm for CX, respectively; 3.6, 4.6 and 6.9 mm for RCA, respectively. Based on the mean displacements, we created a PRV of 3 mm for LM, 4 mm for CX and 5 mm for LAD and RCA. Conclusion: CA showed relevant displacements over the heart cycle, suggesting the need for a specific PRV margin to accurately estimate the dose received by these structures and optimize the planning process.